Changing Trends in the Clinical Presentation and Management of Complete Hydatidiform Mole Among Brazilian Women. Issue 5 (1st June 2016) - Braga, Antonio; Moraes, Valéria; Maestá, Izildinha; Amim Júnior, Joffre; Rezende-Filho, Jorge de; Elias, Kevin; Berkowitz, Ross
Abstract : Objective: The aim of the study was to evaluate potential changes in the clinical, diagnostic, and therapeutic parameters of complete hydatidiform mole in the last 25 years in Brazil. Methods: A retrospective cohort study was conducted involving the analysis of 2163 medical records of patients diagnosed with complete hydatidiform mole who received treatment at the Rio de Janeiro Reference Center for Gestational Trophoblastic Disease between January 1988 and December 2012. For the statistical analysis of the natural history of the patients with complete molar pregnancies, time series were evaluated using the Cox-Stuart test and adjusted by linear regression models. Results: A downward linear temporal trend was observed for gestational age of complete hydatidiform mole at diagnosis, which is also reflected in the reduced occurrence of vaginal bleeding, hyperemesis and pre-eclampsia. We also observed an increase in the use of uterine vacuum aspiration to treat molar pregnancy. Although the duration of postmolar follow-up was found to decline, this was not accompanied by any alteration in the time to remission of the disease or its progression to gestational trophoblastic neoplasia. Conclusions: Early diagnosis of complete hydatidiform mole has altered the natural history of molar pregnancy, especially with a reduction in classical clinical symptoms. However, early diagnosis has not resulted in a reduction in the development of gestational trophoblastic neoplasia, a dilemma that still challenges professionals working with gestational trophoblastic disease.